1987
DOI: 10.1002/aja.1001800105
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of proteins and glycoproteins by perifused rabbit corpus epididymal tubules: Effect of castration

Abstract: Protein synthesis in epididymal tissue of intact and castrated rabbits was studied after incubation of epididymal minces with [35S]-cysteine or [35S]-methionine and protein separation by two-dimensional gel electrophoresis. Regional differences in the pattern of protein synthesized were observed. Castration did not change overall protein synthesis, but it reduced these regional differences. The presence of 5 alpha-DHT in the culture medium of the proximal corpus epididymidis perfused for 24 hr did not increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…An important aspect of epididymal sperm maturation and storage seems to be the interaction of luminal proteins with the surface of spermatozoa [Brooks, 1987;Orgebin-Crist et al, 1987;Hinton et al, 1995;Kirchhoff, 1998]. Therefore, the epididymis of mammals can be studied in different angles: as an organ involved in the maturation of sperm, as a model to study secretory activity, and as an organ responsive to steroidal hormones.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of epididymal sperm maturation and storage seems to be the interaction of luminal proteins with the surface of spermatozoa [Brooks, 1987;Orgebin-Crist et al, 1987;Hinton et al, 1995;Kirchhoff, 1998]. Therefore, the epididymis of mammals can be studied in different angles: as an organ involved in the maturation of sperm, as a model to study secretory activity, and as an organ responsive to steroidal hormones.…”
Section: Discussionmentioning
confidence: 99%
“…So, the threshold requirement of androgen to maintain the structural and functional integrity of the epididymis in the rat, hamster, and monkey is much higher than that needed by the accessory glands (Rajalakshmi et al, 1975). Orgebin-Crist et al (1987) have reported that although the pattern of newly synthesized proteins is not affected in the short term by the presence or absence of androgens in the culture medium of epididymal tubules from intact rabbit, some specific proteins of the caput and corpus epididymidis appeared to be more androgendependent than the cauda epididymidis proteins, with the result that the regional differences in the electrophoretic pattern of normal animals disappear in those castrated.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the functional integrity of the epididymis is androgen-dependent (Blaquier et al, 1972;Orgebin-Crist et al, 1975;Brooks, 1983;Wolf, 1986). There is evidence that sperm maturation will not occur in epididymal tubules cultured in vitro, if androgen dependent proteinsynthesis is blocked by antiandrogen or by inhibitors of RNA or protein synthesis (Orgebin-Crist & Jahad, 1978.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cultured cells, the general immunostaining patterns observed in vivo were maintained during the duration of the primary cultures for all five LIMPs. Our results begin to address the molecular heterogeneity of the lysosomal system along the length of the epidiymis, and may suggest in part a basis for underlying structural and functional characteristics of the epididymis leading to the sequential maturation of sperm.The functions of the epididymis include storage, transport, and provision of a post-testicular site for the maturation of spermatozoa (Bedford, 1975;Hamilton, 1975;Cooper, 1986;Orgebin-Crist, et al, 1987;Robaire and Hermo, 1988). A means by which the epididymis accomplishes these functions is to generate a special luminal fluid that "conditions" the spermatozoa.…”
mentioning
confidence: 99%